2004
DOI: 10.1029/2003jd003666
|View full text |Cite
|
Sign up to set email alerts
|

Global Wildland Fire Emission Model (GWEM): Evaluating the use of global area burnt satellite data

Abstract: [1] The new Global Wildland Fire Emission Model (GWEM) has been developed on the basis of data from the European Space Agency's monthly Global Burnt Scar satellite product (GLOBSCAR) and results from the Lund-Potsdam-Jena Dynamic Global Vegetation Model (LPJ-DGVM). GWEM computes monthly emissions of more than 40 chemical compounds and aerosols from forest and savanna fires. This study focuses on an evaluation of the GLOBSCAR data set. The GWEM version presented here makes use of the Moderate-Resolution Imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
227
5
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(245 citation statements)
references
References 55 publications
8
227
5
1
Order By: Relevance
“…Average fuel consumption on the other hand, was higher in southern hemisphere Africa largely because relatively more fires were detected in woodlands, whereas almost all the fires in northern hemisphere Africa occurred in grasslands with lower percentages of woody vegetation. Other studies have reported lower emissions Barbosa et al, 1999;Hoelzemann et al, 2004), but relatively higher IAV (Barbosa et al, 1999). Some of this difference can probably be attributed to higher fuel loads in our study as our burned area estimates are comparable or even lower than those reported in previous studies.…”
Section: Emissionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Average fuel consumption on the other hand, was higher in southern hemisphere Africa largely because relatively more fires were detected in woodlands, whereas almost all the fires in northern hemisphere Africa occurred in grasslands with lower percentages of woody vegetation. Other studies have reported lower emissions Barbosa et al, 1999;Hoelzemann et al, 2004), but relatively higher IAV (Barbosa et al, 1999). Some of this difference can probably be attributed to higher fuel loads in our study as our burned area estimates are comparable or even lower than those reported in previous studies.…”
Section: Emissionsmentioning
confidence: 95%
“…As burned area estimates improve from higher resolution satellite data and refined algorithms, uncertainties in fuel loads may become the limiting factor in estimating emissions Hoelzemann et al, 2004). Although using satellite data has improved estimates of spatial and temporal variability in fuel loads, approaches for calibrating these estimates using measured values are still in their infancy.…”
Section: Fuel Loadsmentioning
confidence: 99%
“…In Europe corresponding emissions are estimated to be about 1% (65 Kton) of the total inventoried emissions It mainly takes place between 1 and 5 km altitude and mostly in southern Europe (Meijer et al, 2001;Friedrich et al, 2008). The available wild fires estimates range between 20-50 Kt (Friedrich et al, 2009;Hoelzemann et al, 2004) and also occur mostly in countries around the Mediterranean. Given the short life time of NO x and the rather short transport distance of nitrate we assume the impact of lightning and wild land fires can be negligible (<1%) in the Netherlands.…”
Section: Natural Fractionmentioning
confidence: 99%
“…FINNv1 uses MODIS satellite observations for active fires, land cover and vegetation density. The emission factors are from Akagi et al (2011), the estimated fuel loading are assigned using model results from Hoelzemann et al (2004), and the fraction of biomass burned is assigned as a function of tree cover (Wiedinmyer et al, 2006). The Global Fire Assimilation System (GFAS, Kaiser et al, 2012) calculates biomass burning emissions by assimilating Fire Radiative Power (FRP) observations from MODIS at a daily frequency and 0.5 • resolution and is available for the time period 2000-2013.…”
Section: Biomass Burningmentioning
confidence: 99%